Thymalfasin, a promising adjuvant therapy in small hepatocellular carcinoma after liver resection. Issue 16 (April 2017) - He, Chao; Peng, Wei; Li, Chuan; Wen, Tian-Fu
Abstract : Abstract: There is limited information available concerning the effect of thymalfasin (Tα1) as an adjuvant therapy in hepatocellular carcinoma (HCC) patient who received liver resection. The present study aimed to evaluate whether Tα1 can improve the prognosis of small HCC patients after liver resection. A total of 206 patients with small HCC who underwent liver resection were analyzed in our retrospective cohort study. Patients were divided into 2 groups: group A (resection + Tα1, n = 44) and group B (resection, n = 162). Clinical data, overall survival (OS), and recurrence-free survival (RFS) were compared. Prognostic factors were identified using multivariate analysis. After a median follow-up of 47.0 months, 134 patients (65%) had recurrence, and 62 patients (30.09%) died. The 1, 3, and 5-year OS rate of patients in group A was 97.7%, 90.6%, and 82.9%, respectively, and 95.1%, 80.5%, and 62.9%, respectively, for patients in group B ( P = .014). The 1, 3, and 5-year RFS rate of patients in group A was 70.5%, 56.8%, and 53.3%, respectively, and 65.8%, 41.3%, and 32.1%, respectively, for patients in group B ( P = .015). Multivariate analysis indicated that Tα1 was an independent prognostic factor for both OS ( P = .015, hazard ratio 0.349, 95% confidence interval 0.149–0.816) and RFS ( P = .019, hazard ratio 0.564, 95% confidence interval 0.349–0.910). Tα1 as an adjuvant therapy after liver resection may improve the prognosis of small HCC patients after liver resection.